Whitening Domestic Spaces: Enacting Female Roles in Anzia Yezierska’s The Lost Beautifulness - Campos Ferreras, Rebeca (The Grove - Working Papers on English Studies, 2019)
The aim of this research is to give an accurate account of how female stereotypes around the concept of hygiene and domesticity in early 20thC North American context influenced newly arrived Eastern European immigrants. Located in New York’s Lower East Side ghetto and determined by their Jewish background, these immigrants’ arrival caused them a cultural shock to the point that they started shaping their identities according to the new standard of beauty and cleanliness related to the Americanness they were eager to perform. For this purpose, Anzia Yezierska’s short story The Lost Beautifulness serves as a referent because it demonstrates the failure of Americanization as the prospective means through which the American Dream could be experienced, a credo which, according to the author, would only reinforce classist policies instead of cancelling them. To this effect, Yezierska depicts the actual consequences for these Jewish female immigrants after attempting to Americanize their private household spaces and maintain, thus, the standard of cleanliness necessary to validate their accurate adaptation to the American culture from their ghettoized and marginalized context. Keywords: Americanization, Anzia Yezierska, female stereotypes, whitening, domesticity, American Dream